Optimization of antioxidant hydrolysate production from flying squid muscle protein using response surface methodology - Fang, Xubo; Xie, Ningning; Chen, Xiaoe; Yu, Hui; Chen, Jing (Food and bioproducts processing, 2012)
► Hydrolysates from flying squid muscle protein exhibit antioxidative potentials. ► We optimize the hydrolysis condition of the protein. ► Reusing flying squid by-products can enhance economical effectiveness. The squid muscle protein, extracted from by-products of flying squid (Ommastrephes bartrami) was hydrolyzed by five proteases (pepsin, trypsin, papain, alcalase and flavourzyme). DPPH radical scavenging power was used to evaluate antioxidative activity of hydrolysates. The hydrolysate obtained by papain exhibited the most excellent potential of antioxidative activity. Furthermore, response surface methodology (RSM) was employed to optimize hydrolysis conditions, including enzyme to substrate (E/S) ratio, reaction temperature, and hydrolysis time. The optimum conditions obtained were as follows: E/S ratio of 1.74%, temperature of 51°C and time of 46min, under which, DPPH radical scavenging activity of 74.25% was obtained. Moreover, it was found that the optimum hydrolysate of 8mg/mL displayed relatively stronger inhibitory effect on lipid peroxidation compared with α-Tocopherol of 0.1mg/mL.